2022
DOI: 10.1038/s41419-022-05249-y
|View full text |Cite
|
Sign up to set email alerts
|

An update regarding the role of WNK kinases in cancer

Abstract: Mammalian WNK kinases (WNKs) are serine/threonine kinases that contain four members, WNK1–4. They function to maintain ion homeostasis and regulate blood pressure in mammals. Recent studies have revealed that the dysregulation of WNKs contributes to tumor growth, metastasis, and angiogenesis through complex mechanisms, especially through phosphorylating kinase substrates SPS1-related proline/alanine-rich kinase (SPAK) and oxidative stress-responsive kinase 1 (OSR1). Here, we review and discuss the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…While direct implication of Wnk1/WNK1 in MS pathogenesis has been limited to suggestive involvement in phosphorylation differences in B cells as associated with MS susceptibility alleles 101 , the involvement of Wnk1 in CNS dysregulation could represent a potential mechanism for association with monophasic EAE incidence. Interestingly, we identified two nonsynonymous SNPs distinguishing the two major phenotype-associated Wnk1 alleles, both of which change the position of threonine residues ( Table 3 ), providing a potential mechanism of differential post-translational regulation by upstream serine/threonine kinases 102 . Additionally, given the regulation of WNT signaling by WNK1 103 , another intriguing link between our candidate gene prioritization of Wnk1/WNK1 and MS comes from a recent GWAS study of MS relapse hazard, which identified a minor allele in WNT9B as the lead candidate gene driving relapse risk 104 .…”
Section: Discussionmentioning
confidence: 99%
“…While direct implication of Wnk1/WNK1 in MS pathogenesis has been limited to suggestive involvement in phosphorylation differences in B cells as associated with MS susceptibility alleles 101 , the involvement of Wnk1 in CNS dysregulation could represent a potential mechanism for association with monophasic EAE incidence. Interestingly, we identified two nonsynonymous SNPs distinguishing the two major phenotype-associated Wnk1 alleles, both of which change the position of threonine residues ( Table 3 ), providing a potential mechanism of differential post-translational regulation by upstream serine/threonine kinases 102 . Additionally, given the regulation of WNT signaling by WNK1 103 , another intriguing link between our candidate gene prioritization of Wnk1/WNK1 and MS comes from a recent GWAS study of MS relapse hazard, which identified a minor allele in WNT9B as the lead candidate gene driving relapse risk 104 .…”
Section: Discussionmentioning
confidence: 99%
“…This could be because we did not mutate or inhibit the key SLC12A-family members of the 5 expressed in CD4 + T cells, or because other WNK1-regulated ion channels are more important. Beyond the SLC12A-family, WNK kinases have been reported to regulate several other channels including ENaC, CLC3 and TRP6 23 . Further work will be required to address these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the proteomic profiling findings, the majority of phosphokinases were downregulated at CPP-P-or CPP-S treatment (Figure 5). Among the hypophosphorylated kinases were p38α mitogen-activated protein kinase (MAPK14) and c-Jun N-terminal kinases (JNKs) belonging to the MAPK family [71][72][73][74][75], Src-related kinases FGR and Yes, which are responsible for cell proliferation and regulation of endothelial junctional plasticity [76][77][78], glycogen synthase kinase (GSK)-3α/β, a central enzyme involved in carbohydrate metabolism [79,80], lysine deficient protein kinase 1 ("With-no-lysine" kinase 1, WNK1) participating in ion transport and proliferation [81,82], phospholipase C gamma 1 (PLC-γ1) orchestrating phosphoinositide signaling and promoting proliferation [83,84], and p53 kinase, which is responsible for DNA damage repair [85,86] (Figure 5). Upregulated kinases included anti-apoptotic and pro-survival p70 S6 kinase and pro-inflammatory proline-rich Akt substrate of 40 kDa (PRAS40) kinase belonging to the mTOR pathway [87][88][89], mitogen-activated ribosomal S6 kinases (RSK) 1/2/3 [90][91][92], and Chk-2 kinase, which increases cell susceptibility to DNA damage upon being phosphorylated at DNA strand breaks [93][94][95] (Figure 5).…”
Section: Nonementioning
confidence: 99%